2022
DOI: 10.18004/anales/2022.055.03.19
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors and psychometric properties of the Spanish version of the Brief Irritability Test (BITe) in Paraguayan population

Abstract: Agresión (AQ). Resultados: la prueba de Kaiser-Meyer-Olkin (KMO) fue adecuada (KMO=0,880) y la esfericidad se probó significativamente (p<0,001). El análisis confirmatorio confirmó que la escala es unidimensional. El ajuste del modelo fue bueno, según todos los índices de ajuste. El alfa de Cronbach también confirmó una excelente consistencia interna (α=0,91). Las puntuaciones entre las dos escalas (BITe y AQ) han mostrado una buena convergencia (r=0,512; p<0,001). Conclusiones: La versión en español del BITe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…This is consistent with the original English (α = 0.91) and other language (i.e. Turkish α = 0.86, [ 43 ]; French α = 0.80, [ 41 ]; Spanish α = 0.91 [ 42 ]) versions. Multi-group analyses indicated invariance across sex groups in our sample at the configural, metric, and scalar levels.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This is consistent with the original English (α = 0.91) and other language (i.e. Turkish α = 0.86, [ 43 ]; French α = 0.80, [ 41 ]; Spanish α = 0.91 [ 42 ]) versions. Multi-group analyses indicated invariance across sex groups in our sample at the configural, metric, and scalar levels.…”
Section: Discussionsupporting
confidence: 85%
“…Mean total scores found in the present sample were of 13.68. Mean scores reported in previous studies were of 12.95 in Canadian [ 37 ], 12.99 in Turkish [ 43 ], 15.36 in French [ 41 ], and 16.51 in Spanish [ 42 ] populations. These differences in BITe scores may be explained by differences in the samples’ characteristics, by cultural differences specific to each country [ 44 ], and/or by distinct functioning of the BITe across groups and countries [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The COVID-19 pandemic has negatively impacted mental health worldwide (Torales, O’Higgins, et al, 2020). In Paraguay, several studies have reported that the COVID-19 pandemic has caused an increase in perceived stress, irritability, fear, phobia, anxiety, depression, sleep disorders and addictive behaviours in the population, as well as burnout among health care professionals (Barrios et al, 2021, 2022; Ferreira Gould et al, 2021; Figueredo et al, 2022; Torales, Ríos-González, et al, 2020; Torales et al, 2021; Torales, González, et al, 2022; Torales, Ríos-González, et al, 2022). However, research has not measured the level of protective factors for mental health in the general population after the declared end of pandemic by the World Health Organization in the beginning of 2023 (WHO, 2023).…”
Section: Introductionmentioning
confidence: 99%